2004
DOI: 10.1097/01.gim.0000132669.09819.79
|View full text |Cite
|
Sign up to set email alerts
|

Genetic testing for Alpha1-antitrypsin deficiency

Abstract: Purpose: The Alpha Coded Testing Study investigated the risks, benefits, and psychological impact of home genetic testing for ␣ 1 -antitrypsin deficiency. Methods: In the study, 996 adult individuals requested and returned a home-administered, confidential, fingerstick blood test. Results: Individuals highly rated the benefits of establishing a diagnosis (82%), helping family members (86%), and anticipating peace of mind (79%). 78% of 239 current smokers reported a high likelihood of smoking cessation if diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 23 publications
(21 reference statements)
1
22
0
2
Order By: Relevance
“…[17][18][19] Offers for genetic testing made via the mail for alpha-1 antitrypsin deficiency, a smoking-linked form of emphysema, reported an uptake rate of 33%. 9,10 This rate is slightly lower than that found in the GSTM1 studies, but may be a useful comparison for the current study.…”
mentioning
confidence: 44%
See 1 more Smart Citation
“…[17][18][19] Offers for genetic testing made via the mail for alpha-1 antitrypsin deficiency, a smoking-linked form of emphysema, reported an uptake rate of 33%. 9,10 This rate is slightly lower than that found in the GSTM1 studies, but may be a useful comparison for the current study.…”
mentioning
confidence: 44%
“…For example, one trial delivered genetic susceptibility testing for alpha-1 antitrypsin deficiency, a smoking-linked form of emphysema, via the mail to unaffected individuals with some success. 9,10 Results of another trial, in which a computer-based decision-aid enhanced the knowledge of low-risk women with personal or family histories of breast cancer seeking BRCA1/2 susceptibility testing, suggest that such methods could potentially reduce the burden on genetic counselors who are limited in number in the United States and abroad. 11 The Internet may be another promising means to deliver genetic susceptibility testing information and services, though the authors of the above trials rightly caution that research on alternate delivery models is nascent.…”
mentioning
confidence: 99%
“…This approach not only leads to the unambiguous identification of combinations of alleles responsible for ␣ 1 AT deficiency in index patients but also offers the possibility of a risk inventory for their families. This capability is beneficial because recent studies have demonstrated that significant positive effects are associated with the early identification of ␣ 1 AT-deficient individuals (36 ). Importantly, such effects would include an increased willingness to reduce exposure to environmental risk factors, such as cigarette smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Еще одной причиной гибели пациентов с дефицитом А1АТ являются онколо-гические заболевания. Для данной группы пациентов характерно развитие рака печени без предшествующе-го предракового состояния [30,31]. У пациентов с PiZ-аллелью холангиокарциномы, гепатохолангиокарциномы встречаются чаще, чем в общей популяции [4].…”
Section: Discussionunclassified